Type 2 diabetes: Challenges facing GPs. Issue 1 (1st February 2018) - Huo, Lili; Shaw, Jonathan E.
Abstract : China faces a huge task in managing the large numbers of people with diabetes. Primary care is at the forefront of this challenge, and needs to begin to adopt some of the management and organizational approaches that have been shown to be successful in tackling diabetes and similar chronic diseases. Significance statement: China faces a huge task in managing the large numbers of people with diabetes. General practitioners (GPs) are in a privileged position to provide first contact and continuing care for most diabetic patients. However, the GP system in China is still in its infancy and faces a range of challenges, such as a shortage of health care providers, GPs' poor adherence to guideline recommendations, patients' poor adherence to treatment, and lack of access to health care. In this article we describe the challenges that GPs in China are struggling with and some of the management and organizational approaches that have been shown to be successful in tackling diabetes and similar chronic diseases.